Lasmiditan is an effective acute treatment for migraine: A phase 3 randomized study - Kuca, Bernice; Silberstein, Stephen D; Wietecha, Linda; Berg, Paul H; Dozier, Gregory; Lipton, Richard B (Neurology, 2018)
To assess the efficacy and safety of lasmiditan in the acute treatment of migraine. Adult patients with migraine were randomized (1:1:1) to a double-blind dose of oral lasmiditan 200 mg, lasmiditan 100 mg, or placebo and were asked to treat their next migraine attack within 4 hours of onset. Over 48 hours after dosing, patients used an electronic diary to record headache pain and the presence of nausea, phonophobia, and photophobia, one of which was designated their most bothersome symptom (MBS). Of the 1,856 patients who treated an attack, 77.9% had ≥1 cardiovascular risk factors in addition to migraine. Compared with placebo, more patients dosed with lasmiditan 200 mg were free of headache pain at 2 hours after dosing (32.2% vs 15.3%; odds ratio [OR] 2.6, 95% confidence interval [CI] 2.0-3.6, < 0.001), similar to those dosed with lasmiditan 100 mg (28.2%; OR 2.2, 95% CI 1.6-3.0, < 0.001). Furthermore, compared with those dosed with placebo, more patients dosed with lasmiditan 200 mg (40.7% vs 29.5%; OR 1.6, 95% CI 1.3-2.1, < 0.001) and lasmiditan 100 mg (40.9%; OR 1.7, 95% CI, 1.3-2.2, < 0.001) were free of their MBS at 2 hours after dosing. Adverse events were mostly mild or moderate in intensity. Lasmiditan dosed at 200 and 100 mg was efficacious and well tolerated in the treatment of acute migraine among patients with a high level of cardiovascular risk factors. NCT02439320. This study provides Class I evidence that for adult patients with migraine, lasmiditan increases the proportion of subjects who are headache pain free at 2 hours after treating a migraine attack.